(untitled) (Dhaka University Journal of Business Studies, 2023)
Despite a handful of research examining the linkage between job insecurity and affective commitment, the study focuses on the consequences of the COVID-19 pandemic in the educational sector of Bangladesh, especially in the private HEIs (higher educational institutions), which is scant. Job insecurity, a pervasive organizational stressor, is a significant component in workplace counterproductive behavior, which results in a myriad of negative organizational outcomes, including low affective commitment, decreased performance, and so on. Thereby, the study intends to examine the impact of job insecurity on the affective commitment of the faculty members at private HEIs of Bangladesh during COVID-19. Drawing on the organizational identification theory, this study also seeks to evaluate the moderating role of organizational support in the job security and affective commitment linkage where the notion of social exchange theory and betrayal framework are also considered. A crosssectional study is conducted, with data collected conveniently from 204 participants, where the PLS-SEM approach is used to examine the hypothesized relationships. The results reveal a significant negative association between job insecurity and affective commitment, with A significant intervening role of organizational support. More precisely, when respondents perceive a high level of organizational support, they maintain their affective commitment despite the feelings of insecurity. These findings not only shed light on the human resource policies of Bangladeshi HEIs, but also contribute to the existing social exchange and organizational identification theories, as well as the betrayal perspective. Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 183-202